2015
DOI: 10.1080/10410236.2014.940669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Support About Physical Activity on Social Networking Sites: Applying the Theory of Planned Behavior

Abstract: This version is available at https://strathprints.strath.ac.uk/51886/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
1
21
0
3
Order By: Relevance
“…Based on the existing literature (Ajzen, 1991;Ajzen, 2002;Ajzen & Driver, 2009;Zagata, 2012;Zhang et al, 2015;Zhou et. al 2009;Zikic & Saks, 2009) all three considerations that make the theory of planned behavior: attitudes, subjective norms, and perceived behavioral control, can influence the likelihood of the performance of a behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the existing literature (Ajzen, 1991;Ajzen, 2002;Ajzen & Driver, 2009;Zagata, 2012;Zhang et al, 2015;Zhou et. al 2009;Zikic & Saks, 2009) all three considerations that make the theory of planned behavior: attitudes, subjective norms, and perceived behavioral control, can influence the likelihood of the performance of a behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, for students to be more engaged with social media in their classes, they need to have a positive attitude about using social media. Zhang et al (2015) showed that attitudes and perceived behavioral control were important considerations to enact change on student intentions. Based on the results of the study, the positive attitudes held by the students is based on the idea of voluntariness.…”
Section: Rqmentioning
confidence: 99%
“…Another important variable in terms of physical activity from the perspective of SCT is SS. Studies have indicated that SS in the general population critically influences the participation of individuals in physical activity (Draper, Grobler, Micklesfield, & Norris, ; Mendonça & Farias Júnior, ; Zhang et al., ). Other studies have also indicated the importance of social interaction in promoting physical activity in those with SMDs (Gray et al., ; Hoffmann et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, young adults liked receiving personalized health information about the HPV vaccine from peers on SNSs [3]. Further, social support from peers on SNSs can indirectly increase college students’ intentions to participate in leisure-time physical activity (LTPA) [4]. Here, LTPA refers to a specific domain of physical activity in which people engage voluntarily during their free time because of physical activity has the potential to provide feelings of enjoyment, control, or mastery [5,6].…”
Section: Introductionmentioning
confidence: 99%